Faktor-Faktor yang Mempengaruhi Penggunaan BBM oleh Toko Online di Indonesia - Deny, Deny (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2016)
This study was conducted to answer the question of what is the factors affecting decision to use BBM (BlackBerry Messenger) to support online store business. With SME’s online store booming in Indonesia, this research was specially studied SME’s and micro online store as subject. Survey has been conducted by BBM chat message and online web page to SME’s online store that using BBM in Indonesia. A total of 187 valid respondents from 18 provinces and 58 cities in Indonesia responded to the survey. Analysis was conducted using SEM method with Lisrel 8.7 support which tested the 8 hypotheses. The result indicated that there are positive significant effects of perceived usefulness, perceived playfulness and trust toward BBM use intention for online store. However, this study didn’t find direct significant effects of perceived ease-of-use toward use intention. Perceived ease-of-use found to have significant indirect effect through the mediation effect of perceived playfulness. In fact, perceived playfulness is the main factor influencing the use intention of BBM for SME’s online store. This founding give insight for application developers to consider playfulness in developing social media applications for online business. Keywords: TAM, BBM, SME, media social marketing